Analisis Faktor-faktor yang Memengaruhi Permintaan Cabai Merah Besar Pada Rumah Tangga di Kecamatan Purworejo Kabupaten Purworejo - Hasbitsaany, Muhammad; Roessali, Wiludjeng; Nurfadillah, Suryani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Big red chili is a horticultural commodity with relatively high demand and price fluctuations. This study aims to analyze the average consumption of big red chili, analyze the factors affecting demand for big red chili and examine elasticity of demand for big red chili on households in Purworejo District, Purworejo Regency. The research was conducted from November 2024 to Februari 2025 at Purworejo Market, Baledono Market, Pagi Liwung Tambakrejo Market, and Pangenrejo Market. The research method used a survey with non-probability sampling technique, specifically accidental sampling, involving 96 respondents who met predetermined criteria. Data analysis was conducted using multiple linear regression analysis and demand elasticity analysis. The result indicate average consumption of big red chili in Purworejo District, Purworejo Regency is 0.24 kg/capita/month. multiple linear regression analysis shows the variables of big red chili price, curly red chili price, shallot price, household income, number of family members, and consumer preference collectively have significant effect on demand for big red chili. Partially, the variables of curly red chili price, number of family members, and consumer preference have significant effect, while the variables of big red chili price, shallot price, and household income do not have a significant effect on demand for big red chili in Purworejo Regency. Price elasticity of big red chili is 0.24, indicating that it is inelastic, cross-elasticity of curly red chili price is 0.39, indicating substitute good, cross-elasticity of shallots is -0.08, indicating a complementary good, income elasticity is 0.01, indicating big red chili a normal good.